1993
DOI: 10.1159/000284819
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Diagnoses in Various Psychiatric Disorders: A Study of Long-Term Course

Abstract: The frequency of diagnostic shift was investigated in 267 patients diagnosed with various psychiatric disorders according to the 9th revision of the International Classification of Diseases (ICD-9). Forty-six patients fulfilled the diagnostic criteria for schizophrenic psychosis, 71 for affective psychosis, 66 for neurotic disorder, 24 for personality disorder, and 40 for psychogenic reaction. The remaining 20 patients were diagnosed with heterogenous disorders. The mean follow-up time was 12.5 years. Every ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 13 publications
(20 reference statements)
3
11
0
Order By: Relevance
“…Psychotic disorder and bipolar disorder were the most stable categories, whereas anxiety disorder and adjustment disorder were less stable. These results are comparable with previous studies [2,[6][7][8], in which psychotic conditions were the most stable, whereas 'neurotic' and affective diagnoses were more subject to change. Adjustment disorder was the weakest diagnostic group.…”
Section: Stability Of Diagnosessupporting
confidence: 90%
See 2 more Smart Citations
“…Psychotic disorder and bipolar disorder were the most stable categories, whereas anxiety disorder and adjustment disorder were less stable. These results are comparable with previous studies [2,[6][7][8], in which psychotic conditions were the most stable, whereas 'neurotic' and affective diagnoses were more subject to change. Adjustment disorder was the weakest diagnostic group.…”
Section: Stability Of Diagnosessupporting
confidence: 90%
“…Kaelbling and Volpe [1] studied 934 patient records and found a stability of about 66% in the different diagnostic groups. Since then, other studies have been made on this topic, either from case registers [2][3][4], from medical records [1,5,6], or from patient interviews [7,8]. Overall, the diagnostic stability ranged from 60 to 80%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaglum, Friis, Karterud, Mehlum, & S. Vaglum, 1993;Vetter & Koller, 1993). Cross-sectional findings have similarly indicated that the prevalence of personality disorder traits declines with age among adolescents and adults (e.g., Kessler et al, 1994;Robins & Regier, 1991;Samuels et al, 2002).…”
Section: Hypotheses Regarding How Childhood Adversities May Contributmentioning
confidence: 98%
“…Fanous et al (2007) [19] examined the interaction between major depression and neuroticism based on a sample of male twins, and found that major depression may have a direct causal effect on neuroticism. Both literatures [20, 21] and clinical experiences suggest that the stability and the course of PSD and MAD were quite different. Therefore, we suppose that the trajectory of PD traits across age may differ from a typical trajectory in the presence of co-occurring Axis I disorders that share similar clinical characteristics.…”
Section: Introductionmentioning
confidence: 99%